Study Brand Trust, Brand Extension And Brand Loyalty Product Eiger Lamongan Store - Sani Rusminah; Irdam Rahmat Dani (Sean Institute, 2024)
This research was conducted starting from the many considerations from the people in Lamongan, especially ordinary people and users of Eiger brand products about the rampant competition of outdoor brands which is increasing day by day. The purpose of this study was to analyze the influence of brand trust, brand extension and brand loyalty variables on purchasing decisions for Eiger store Lamongan products. This study uses descriptive research with a quantitative approach, for the population itself is unknown or sampling through non-probability sampling, namely the purposive sampling method involving 255 respondents. The data collection method uses the distribution of online questionnaires google form. The data analysis technique is processed with a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) from SmartPLS version 4.0. The results of this study indicate that brand trust has a positive and significant effect on purchasing decisions for Eiger Lamongan brand products with a T-statistic value of 4.004. Brand extension has a positive and significant effect on purchasing decisions for Eiger Lamongan brand products with a T-statistic value of 4,028 and brand loyalty has a positive and significant effect on purchasing decisions for Eiger Lamongan brand products with a T-statistic value of 3,793.